2020
DOI: 10.1088/1361-6463/ab9ce3
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise in high performance and stability of Li-doped ZnO thin-film transistors

Abstract: In this work, thin film transistors (TFTs) based on the ZnO-doped with different concentrations of Li were fabricated by radio frequency sputtering. Using the optimal Li doping concentration of 1% and rationally designed passivation layer (PVL), a TFT with high mobility of 28.5 cm2/Vs, low SS of 0.28 V decade−1, high Ion/Ioff of 107 and small Vth of 0.8 V were obtained. Moreover, the 1% Li-doped ZnO TFT with Al2O3 PVL exhibits the best stability with the small Vth shifts of 1.1 (− 1.2) V and 1.6 (− 1.8) V unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…According to the equation, N e increases with the negative shift of V th after increasing the Ar gas flow rate. Furthermore, this result also demonstrated that the mobility of our oxide semiconductor devices is strongly dependent on the carrier concentration on the channel layer . Carrier transport is regulated by percolation conduction through the trap states, and filling the trap states increases the carrier movement at high concentrations .…”
Section: Results and Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…According to the equation, N e increases with the negative shift of V th after increasing the Ar gas flow rate. Furthermore, this result also demonstrated that the mobility of our oxide semiconductor devices is strongly dependent on the carrier concentration on the channel layer . Carrier transport is regulated by percolation conduction through the trap states, and filling the trap states increases the carrier movement at high concentrations .…”
Section: Results and Discussionsupporting
confidence: 53%
“…From the table, the SS average values of Ar 50, 75, and 100 samples are 0.24 ± 0.03, 0.23 ± 0.07, and 0.39 ± 0.26 V/dec, respectively. SS is correlated with the D it of the oxide TFTs and was estimated from this equation: , D it = C ox q SS log ( e ) k normalB T q 1 where k B is Boltzmann’s constant, T is the absolute temperature, and q is charge of an electron. Based on the above equation, the D it values of the Ar 50 sample and the Ar 75 sample were found to be 1.44 × 10 13 and 1.38 × 10 13 cm –2 eV –1 , demonstrating that the D it of the a-IZO TFTs is reduced by increasing the Ar flow rate.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also from Figure a, it can be noted that the normalized drain current noise power spectral density tends to decrease as the oxygen pressure increases. This predicts a decrease in the average defect trap state density in the bulk and surface of α-IGZO film. , This also indirectly proves that UV-ORTA treatment is effective in reducing α-IGZO film defects.…”
Section: Resultsmentioning
confidence: 59%
“…This predicts a decrease in the average defect trap state density in the bulk and surface of α-IGZO film. 54,55 This also indirectly proves that UV-ORTA treatment is effective in reducing α-IGZO film defects.…”
Section: Resultsmentioning
confidence: 99%